Covalent immobilization of VEGF on allogeneic bone through polydopamine coating to improve bone regeneration - Huang, Jianhao; Lu, Jingwei; Liu, Ziying; Jin, Jing; Xie, Chunmei; Zheng, Yang; Wang, Zhen; Yu, Lingfeng; Zhu, Yan; Fan, Gentao; Sun, Guojing; Xu, Zhihong; et al. (Frontiers in Bioengineering and Biotechnology, 2022)
Objective: Promoting bone regeneration and repairing in bone defects is of great significance in clinical work. Using a simple and effective surface treatment method to enhance the osteogenic ability of existing bone scaffold is a promising method. In this article, we study the application of catecholic amino acid 3,4-dihydroxyphenylalanine (DOPA) surface coating chelated with vascular endothelial growth factor (VEGF) on allogeneic bone. Method: Allogeneic bone is immersed in DOPA solution and DOPA form polydopamine (PDA) with good adhesion. Electron microscopy is used to characterize the surface characteristics of allogeneic bone. MC3T3-E1 cells were tested for biocompatibility and osteogenic signal expression. Finally, a 12-week rabbit bone defect model was established to evaluate bone regeneration capability. Results: We found that the surface microenvironment of DOPA bonded allogeneic bone was similar to the natural allogeneic bone. VEGF loaded allografts exhibited satisfying biocompatibility and promoted the expression of osteogenic related signals in vitro. The VEGF loaded allografts healed the bone defect after 12 weeks of implantation that continuous and intact bone cortex was observed. Conclusion: The PDA coating is a simple surface modification method and has mild properties and high adhesion. Meanwhile, the PDA coating can act on the surface modification of different materials. This study provides an efficient surface modification method for enhancing bone regeneration by PDA coating, which has a high potential for translational clinical applications.